2022
DOI: 10.1007/s10654-022-00919-9
|View full text |Cite
|
Sign up to set email alerts
|

A population-based cohort study of sex and risk of severe outcomes in covid-19

Abstract: There is a male sex disadvantage in morbidity and mortality due to COVID-19. Proposed explanations to this disparity include gender-related health behaviors, differential distribution of comorbidities and biological sex differences. In this study, we investigated the association between sex and risk of severe COVID-19 while adjusting for comorbidities, socioeconomic factors, as well as unmeasured factors shared by cohabitants which are often left unadjusted. We conducted a total-population-based cohort study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
0
9
1
Order By: Relevance
“…Males typically experience more frequent lower respiratory tract infections [ 112 ] and, in the case of influenza A and B viruses, RSV, SARS-CoV, and other sources of community-acquired pneumonia, more severe disease compared to females [ 113 , 114 ]. Similarly, with SARS-CoV-2 infection, males are hospitalized [ 8 , 115 ], are admitted to intensive care unit (ICU) [ 8 , 116 ] and die [ 117 , 118 ] more often, although infection rates appear to be similar to those of women [ 119 ]. Sex-disaggregated estimates of the infection fatality ratio show consistently higher fatality rates among males in every age category [ 8 , 9 ].…”
Section: Host Factorsmentioning
confidence: 99%
“…Males typically experience more frequent lower respiratory tract infections [ 112 ] and, in the case of influenza A and B viruses, RSV, SARS-CoV, and other sources of community-acquired pneumonia, more severe disease compared to females [ 113 , 114 ]. Similarly, with SARS-CoV-2 infection, males are hospitalized [ 8 , 115 ], are admitted to intensive care unit (ICU) [ 8 , 116 ] and die [ 117 , 118 ] more often, although infection rates appear to be similar to those of women [ 119 ]. Sex-disaggregated estimates of the infection fatality ratio show consistently higher fatality rates among males in every age category [ 8 , 9 ].…”
Section: Host Factorsmentioning
confidence: 99%
“…Bearing in mind that life expectancy is increasing worldwide and even at a faster rate in less-off parts of the world [ 73 ], given the challenges posed by ageing societies, low-income countries, which endured the most devastating effects of the COVID-19 pandemic, should be urged to estimate the relationships investigated here. Multimorbidity manifests differently across age and sex groups [ 74 ], as appears to be the case for the COVID-19 outcomes [ 11 , 75 ]. The studies identified in our review did not provide stratified estimates for these groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, in some patients, a dysfunctional response leads to an intense increase in cytokine release, the cytokine storm, leading to septic shock and multiorgan failure 25 , 26 . In this regard, the differences in immunological response between sexes have been hypothesized to explain increased severity risk in males 27 .…”
Section: Discussionmentioning
confidence: 99%